The students’ perceptions of their online learning - Nila Kesumawati; Nyiayu Fahriza Fuadiah; Budi Utomo (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study intends to determine the perceptions of the in-service Teacher profession education program (PPG) students towards Indonesian network learning system (SPADA) hybrid learning. This study employed a survey method with a qualitative approach. Subjects in this study were 82 of 87 PPG Daljab 1 Batch 1 students. The technique of collecting data was through the instruments of questionnaires and interviews. The questionnaire was used to obtain data about the quality of online content and the assessment of online learning that has been carried out. Interviews were conducted to confirm the results of the questionnaire data to see the compatibility between the two data. Data analysis techniques in this study were conducted qualitatively and quantitatively by considering to the research objectives. The results showed that online learning had sharp quality content, can be accepted and well understood, easy to operate and use, overcomes distance and time constraints, and has benefits that are in line with the objectives of PPG implementation.